2015
DOI: 10.3109/14647273.2014.995240
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and demographic correlates of the discontinuation ofin vitrofertilization

Abstract: In this study, we investigated the relationship between psychosocial factors assessed pre-treatment and the discontinuation of in vitro fertilisation (IVF) treatment after one year. A cohort study was performed in a Dutch fertility clinic and included 667 couples. Demographic characteristics, scores for psychosocial factors, discontinuation rates, reasons for discontinuation and outcome data of the treatment were measured. Discontinuation due to personal reasons was differentiated from discontinuation because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…One of them has identified female depression as an important predictor of discontinuation [15]. Another found that female depression is not a predictor of discontinuation [24]. However, this latter study has a reduced number of discontinuers comparing with continuers, which can create a bias in the predicting power of the analysis.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…One of them has identified female depression as an important predictor of discontinuation [15]. Another found that female depression is not a predictor of discontinuation [24]. However, this latter study has a reduced number of discontinuers comparing with continuers, which can create a bias in the predicting power of the analysis.…”
Section: Discussionmentioning
confidence: 95%
“…First, using the couple as the unit of analysis enables the research to account for the non-independence of the data and mutual influence of each member of couples [40]. Second, this study adds to our understanding of how fertility centers and medical staff can be more sensitive to aspects that can undermine fertility care continuity, suggesting that couples should be screened for psychopathology at the beginning of treatment [15,24]. Couples with an older or clinically depressed female partner should be specifically targeted for counseling concerning the importance of compliance within MAR treatments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations